A numerical study on effects of swirl and primary aeration of fuel jet on pollutant emissions in a swirl burner - Manjunath, B.C.; Shet, U.S.P.; Raghavan, V. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.